Traumatic hyphema in children and adolescents – aetiology and treatment - Urban, Beata; Bakunowicz-Łazarczyk, Alina; Michalczuk, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Purpose : Retrospective analysis of patients with traumatic hyphema, including type of injury, treatment and visual outcome. Material and methods : We analysed a cohort of patients after blunt trauma, who were examined and treated between 2011– –2015. In each case, the baseline and ultimate visual acuity was determined, followed by slit lamp examination, intraocular pressure measurement, indirect binocular ophthalmoscopy of the fundus, ultrasound scan and OCT Visante. The type of treatment as well as duration of inpatient treatment and late complications were assessed for each case. Results : 45 patients (45 eyes) with traumatic hyphema due to blunt ocular trauma were enrolled. 42 of them were boys (93.3%), and 3 were girls (6.7%). The age range was 2.5–17.5 years (mean age of 11.92 ± 3.75 years). Upon admission, 10 (22.2%) children had full visual acuity (1.0). The most common injuries concomitant with hyphema included iridodialysis, corneal oedema, mydriasis and corneal erosion. Secondary hemorrhage occurred three days following injury in only one (2.2%) patient. The mean duration of inpatient admission was 4.3 days (ranged from 2 to 8 days). At the last follow-up visit, 36 (80%) patients had a full visual acuity of 1.0. Conclusions: Visual outcomes improve with earlier treatment commencement. Conservative management was sufficient to resolve traumatic hyphema in reported cases.